Torsional capacity of prestressed assembled quarter-shell concrete tower with adhesive bonded vertical joints - Wei-Feng Tao; Dorjee TseDan; Dong-Liang Zhang; Ci-Rong Huang; Kun Fu; Chu Zhao; Jia-Wei Zhang; Jun-Lin Li; Zhi-Qiang Wan (Case Studies in Construction Materials, 2025)
Prestressed assembled concrete tower with adhesive bonded vertical joints is currently a prevailing type of supporting structure of large-scaled onshore wind turbines. However, few works have been done to study the effect of the adhesive bonding on the mechanical behavior of this type of concrete towers. In this paper, the failure mechanism and torsional capacity of a quarter-shell concrete tower with adhesive bonded vertical joints were studied through finite element analysis. The failure sequences of the vertical joints in two typical load cases along with their influence on the stress distributions on the horizontal joints were discussed in detail. In addition, the torsional capacities evaluated by the free torsion model and constrained torsion model were compared with the simulation results, and the differences among them were explained. It was found that in the nonlinear stage of torsion, the compressive stress distributions on the horizontal joints no longer comply with the plain section assumption, and it is inappropriate to regard the concrete segments as thin-walled members. The constrained torsion model can be employed to evaluate the torsional capacity of whole ring towers quite well, but does not apply to quarter-shell towers. The torsional capacity of the quarter-shell tower is determined by the strengths of the vertical joints in several segments below the position of variable cross-section, rather than by the strengths of the horizontal joints. The results presented in this paper are expected to facilitate more rational design of concrete towers in the wind power industry.